The relationship between nature exposure and depression among Chinese prisoners: a moderated mediation model - Zeng, Yuze; Zhang, Qingqi; Yan, Jinglu; Qi, Ke; Ma, Ai; Liu, Xiaoqian; Xiao, Junze (Frontiers in Psychology, 2024)
Aim This study examined the association between self-reported nature exposure and depression among Chinese prisoners, as well as the mediating and moderating effects of meaning in life and callous-unemotional (CU) traits, respectively. Background Prisoners are more likely to experience depression than any other mental illness. Exposure to nature has been proposed as a highly cost-effective method of treating their depressive symptoms. However, the mechanism underlying the link between nature exposure and depression among prisoners needs further investigation, as the findings may provide new insights into how to address depression in incarcerated populations. Method Data were collected through a survey conducted in four prisons in southern China from April to May 2022. The participants were 574 prisoners who anonymously completed four questionnaires about nature exposure, meaning in life, depression, and CU traits. Results The results show that: (1) meaning in life significantly mediates the association between nature exposure and depression, and (2) CU traits moderate the connection between nature exposure and meaning in life. Conclusion The current study uncovered that prisoners who contact more with the natural environment have a higher meaning in life and lower depression, and individuals with higher CU traits can benefit more from nature exposure.